Pengaruh Kompetensi Guru Dalam Proses Pembelajaran dan Motivasi Belajar Terhadap Prestasi Belajar Fisika - Mujiyono, Mujiyono (Jurnal Dewantara, 2017)
The research population in this study were all second grade Junior High School three classes with the number of students 115 students. Samples taken in this study consisted of two the number of students 69 students were taken by using random sampling techniques. There is a significant impact on the competence of teachers in the learning process and learning motivation on learning achievement physics students either jointly or respectively on the real level of 5% and 1%; in the competence of teachers in the learning process and learning motivation toward students' physics learning achievement of 36.05%; in the competence of teachers in the learning process of the students' physics learning achievement of 17.26%; and the contribution of learning motivation toward students' physics learning achievement of 19.01%.